The association of Cribra orbitalia and Porotic hyperostosis with respiratory diseases in a Western Cape population - Marais, Chantelle (Stellenbosch : Stellenbosch University, 2024)
Marais, Chantelle. 2024. The Association of Cribra Orbitalia and Porotic Hyperostosis with Respiratory Diseases in a Western Cape Population. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available:https://scholar.sun.ac.za/items/021c5137-5f02-4ca6-b7a6-3ea2adad9d31